Study of the alkaline earth metals with 8-hydroxyquinolinate derivatives - Calcium complexes - Guerreiro, CTR; Ribeiro, Clovis Augusto [UNESP]; Crespi, Marisa Spirandeli [UNESP] (Kluwer Academic Publ, 2002)
Metal complexes of calcium with 5,7-dibromo, 7-iodo and 5-chloro-7-iodo-8-hydroxyquinolate were precipitated in aqueous ammonia and acetone medium, except for the solid state compound with 5,7-dichloro-8-hydroxyquinoline which hasn't been obtained under these conditions. The complexes obtained through the mentioned precipitation are Ca[(C9H4ONBr2)(2)](3).H2O, Ca[(C9H5ONI)(2)].2H(2)O and Ca[(C9H4ONICl)(2)].2.5H(2)O. Their intermediate from the thermal decomposition found through TG/DTA curves in air indicated the presence of different kinds of calcium carbonates related to the reversibility and crystalline structure, depending on the original compounds. The initial compounds and the intermediate from the thermal decomposition were also characterized through IR spectra and X-ray diffraction.
Keywords: calcium; DTA; 8-hydroxyquinolinate derivatives; TG; thermal behavior